SAT0313 Relationship Between Sustained Lowering of Serum Urate Levels and Improvements in Gout Flares and Tophus Area: Pooled Exploratory Analysis of Gout Subjects Receiving Lesinurad and Xanthine Oxidase Inhibitor Combination Therapy. (9th June 2015) - Terkeltaub, R.; Perez-Ruiz, F.; Storgard, C.; Fung, M.; Kopicko, J.; Dalbeth, N.
Abstract : Background: Previous studies have shown that long-term urate-lowering therapy is required for improvements in gout flare frequency and tophi reduction, and that lower serum uric acid (sUA) levels may result in greater benefit. However, optimal sUA levels to jointly achieve these outcomes within a year using single or combination oral therapies are uncertain. Objectives: To assess the impact of sustained sUA lowering to determine if the magnitude of continual low sUA levels results in greater tophus size reduction and fewer patients experiencing gout flares requiring treatment (GFRT). Methods: Patients, irrespective of treatment assignment, were combined from 3 Phase III clinical studies examining the efficacy of lesinurad, a selective uric acid reabsorption inhibitor (SURI), in combination with a xanthine oxidase inhibitor (allopurinol: CLEAR 1 [NCT01510158 ], CLEAR 2 [NCT01493531 ]), or febuxostat: CRYSTAL [NCT01510769 ]). For this analysis, GFRTs were assessed during the last quarter of study treatment (end of Month 9 to end of Month 12) and reduction in target tophus area (measured using Vernier calipers) was assessed over the duration of the study. Patients were categorized by on-study median sUA levels of ≥6, 5–<6, 4–<5, 3–<4, and <3 mg/dL. On-study median sUA is defined as the median of an individual subject's scheduled post-baseline sUA measurements, regardless of number of post-baseline measurements present. Results: In total, 1537 patients were eligible for analysis; 95% were male, 78% were white, and mean (SD) age was 42 (11) years. A total of 474 patients (30.8%) had ≥1 target tophi that were followed in the studies. A positive relationship between lower sUA and greater tophus area reduction and GFRT was observed. In patients with ≥1 target tophi at baseline in the 3 studies, those with lowest on-study median sUA levels achieved greatest reduction in tophus area (Fig. 1A ). Patients with median sUA <3.0 mg/dL had ∼60% mean reduction in tophus area at Month 12 compared with 28% for those with sUA of 5.0 – <6.0 mg/dL. Similarly, those with lower sUA levels were less likely to have GFRT. During the last quarter of the study, 12.2% with median sUA <3.0 mg/dL experienced a GFRT, compared with 20.5% with median sUA of 5.0-<6.0 mg/dL (Fig. 1B ). Conclusions: These findings demonstrate that degree of clinical benefit (reduction in GFRT or tophus area) within 12 months correlates with the magnitude of sustained sUA lowering using oral sUA-lowering therapy. The results provide additional confirmation of the validity of sUA lowering as a surrogate for clinically meaningful effects in gout patients and point to potential benchmarks. In this context, patients with median sUA <3.0 mg/dL had approximately double the mean reduction in tophus area at Month 12 compared with sUA 5.0 – <6.0 mg/dL and approximately 40% lower GFRT in the last quarter of the study. Acknowledgements: This study was funded by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and was funded by AstraZeneca. Disclosure of Interest: R. Terkeltaub Consultant for: Ardea Biosciences, AstraZeneca, Takeda, Relburn, REVIVE, F. Perez-Ruiz Consultant for: Menarini, AstraZeneca, Pfizer, Speakers bureau: Menarini, AstraZeneca, Pfizer, C. Storgard Shareholder of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., M. Fung Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., J. Kopicko Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., N. Dalbeth Grant/research support from: AstraZeneca, Fonterra, Novartis, Speakers bureau: Savient, Menarini, Novartis, Teijin, and Advisory Boards for AstraZeneca, Fonterra, Takeda, Pfizer, Metabolex